2010
DOI: 10.1159/000318813
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Schizophrenia: Reliability of an Operationalized Approach to ‘Praecox-Feeling’

Abstract: Background: H.C. Rumke coined the term ‘praecox-feeling’ to denote a specific unease experienced by the clinician reflecting the ‘impossibility of empathy’ and ‘lack of exchange of affect’ that has been reported to occur early on when examining schizophrenia patients. There is ample evidence that praecox-feeling is still relevant in modern clinical practice. This study examined the reliability of operationalized praecox-feeling against the background of modern diagnostic criteria and assessment methods. Sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Despite being used in everyday clinical practice [56,57], the concept of intuitive knowledge as put forth by classical psychopathology has not been empirically tested, except for the putative schizophrenia-specific ineffable intuition named ‘Praecox Gefühl[' 58], which has been the object of a few studies that gave inconclusive results [59,60,61]. In psychotherapy research, a number of studies attempted to explore the relationship between the therapist's feelings and the patient's diagnosis or symptoms [62,63,64,65,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being used in everyday clinical practice [56,57], the concept of intuitive knowledge as put forth by classical psychopathology has not been empirically tested, except for the putative schizophrenia-specific ineffable intuition named ‘Praecox Gefühl[' 58], which has been the object of a few studies that gave inconclusive results [59,60,61]. In psychotherapy research, a number of studies attempted to explore the relationship between the therapist's feelings and the patient's diagnosis or symptoms [62,63,64,65,66,67].…”
Section: Introductionmentioning
confidence: 99%
“…In psychiatric literature, there are many terms that refer to this experience; the most popular and articulated conceptualizations are undoubtedly Rümke's Praecox Gefühl [9], Wyrsch's Diagnosis through Intuition [10], Minkowski's Diagnostic par Pénétration [11], Binswanger's Diagnosis through Feeling [12], and Tellenbach's Atmospheric Diagnosis [13]. Of these, only Rümke's Praecox Feeling was empirically tested, although with conflicting results: one study found a good diagnostic precision of such intuitive reasoning [14] whereas another yielded inconclusive findings [15]. These discrepant findings may be related to different definitions of the concept itself and to the methodological approaches used.…”
Section: Introductionmentioning
confidence: 99%
“…To unfold this paradox, we wanted to submit the account of a clinical encounter from the perspective of the clinician. Very few recent studies had been made to explore the reliability and validity of Praecox Feeling as a diagnostic tool in clinical practice (Wiggins, 1987;Grube, 2006;Ungvari, 2010). These researches had intended to compare Praecox…”
Section: Methodsmentioning
confidence: 99%